Beetroot juice supplementation and exercise performance: is there more to the story than just nitrate? - Zoughaib, William S.; Fry, Madison J.; Singhal, Ahaan; Coggan, Andrew R. (Frontiers in Nutrition, 2024)
This mini-review summarizes the comparative effects of different sources of dietary nitrate (NO3 -), beetroot juice (BRJ) and nitrate salts (NIT), on physiological function and exercise capacity. Our objectives were to determine whether BRJ is superior to NIT in enhancing exercise-related outcomes, and to explore the potential contribution of other putatively beneficial compounds in BRJ beyond NO3 -. We conducted a comparative analysis of recent studies focused on the impact of BRJ versus NIT on submaximal oxygen consumption (VO2), endurance performance, adaptations to training, and recovery from muscle-damaging exercise. While both NO3 -sources provide benefits, there is some evidence that BRJ may offer additional advantages, specifically in reducing VO2 during high-intensity exercise, magnifying performance improvements with training, and improving recovery post-exercise. These reported differences could be due to the hypothesized antioxidant and/or anti-inflammatory properties of BRJ resulting from the rich spectrum of phytonutrients it contains. However, significant limitations to published studies directly comparing BRJ and NIT make it quite challenging to draw any firm conclusions. We provide recommendations to help guide further research into the important question of whether there is more to the story of BRJ than just NO3 -.